Influence of the fast neutron irradiation on the IR-LEDs reliability; ISROS 2014 - Gradoboev A. V. Aleksandr Vasilyevich; Orlova K. N. Kseniya Nikolaevna; Asanov I. A.; Salchak Y. A. (2014, 2014)
В фонде НТБ ТПУ отсутствует